THE EFFECT OF DEPOSITION TEMPERATURE ON Cu2ZnSnS4 (CZTS) THIN FILMS GROWN BY DC MAGNETRON SPUTTERING - Fianti Fianti; Shila Artha Mulia; Nabila Rizkina Sari; Siti Firdhosiyah; Budi Astuti; Putut Marwoto; Kyoo Ho Kim; Muhammad Ikhlasul Amal; Ersan Yudhapratama Muslih (Indonesian Physical Review, 2026)
Cu₂ZnSnS₄ thin films were successfully deposited on soda lime glass substrates using the DC Magnetron Sputtering method at a plasma power of 42 W, an argon gas pressure of 500 mTorr, and deposition temperatures ranging from 27 °C to 400 °C for 7 hours, using a Cu₂ZnSnS₄ target with 99% purity. The effect of varying temperatures was characterized by using X-ray Diffraction (XRD) to determine the film structure, Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDX) to analyze morphology and composition, and UV-Vis-NIR spectrophotometry to evaluate optical properties. Film composition showed non-stoichiometric characteristics, with elemental ranges of Cu (20.66–32.81) %, Zn (14.08–25.67) %, Sn (21.87–37.05) %, and S (25.42–31.22) %. All samples exhibited a Cu/(Zn+Sn) ratio of less than 1, indicating Cu-poor compositions typical of p-type semiconductors. XRD analysis revealed that the formation of the Cu₂ZnSnS₄ phase began at a deposition temperature of 100 °C, while stable kesterite Cu₂ZnSnS₄ crystals were obtained at 400 °C, corresponding to the (112) crystal plane. The absorption coefficients and band gap energies ranged from 10⁴ to 10⁵ cm ¹ and from 1.34 to 2.175 eV, respectively, confirming the suitability of the films for solar cell applications. SEM observations indicated that higher deposition temperature promoted more successful grain growth. Overall, higher deposition temperatures yield better Cu₂ZnSnS₄ thin films.